Bioactive nanomaterials for ion‐interference therapy. Issue 2 (25th May 2020) - Liu, Yanyan; Zhang, Meng; Bu, Wenbo
Abstract: Ions with biological actions have been exploited to perform a wide range of tasks, including antitumor therapy, termed ion‐interference therapy (IIT). However, single ions or ion‐containing small molecules possess serious limitations for in vivo therapeutic applications due to their short circulation duration, weak discrimination between healthy and tumor tissues, and dose‐limiting systemic toxicity. Bioactive nanomaterials, not only successful targeting tumors but also sufficient generation/release of active species for cell death induction, have attracted enormous interest in IIT due to their potential to tackle the challenges, and are largely the focus of this review. Abstract : The aberrant distribution/accumulation of ions in cells can interfere with many important biological processes, inducing irreversible physical damage to cells or the activation of biochemical reactions for cytotoxic ingredients generation, namely, ion‐interference therapy (IIT). Bioactive nanomaterials have attracted enormous interest in IIT due to their potential to tackle the challenges that are otherwise difficult for single ions or ion‐containing small molecules. This review focuses on the selection of therapeutic ions, the design and preparation of bioactive nanomaterials, and the proposition of anticancer principles to present an overview of IIT.